Transforming School Climate through the Support of a Compassionate Character-Based Love Curriculum at Madrasah Aliyah - Hepy Septiani; Meilisa Sajdah; Anwar Sanusi; Neli Farhataini; Faizah Hayat; Romli Romli (BASICA, 2025)
This study aims to analyze the transformation of the school climate through the mentoring of the Love Curriculum based on the character of compassion at MA Al-Islamiyah. The study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that first, the implementation of the Love Curriculum is carried out through the integration of the value of compassion in learning activities, the school's religious culture, the habit of politeness, respect for teachers, and strengthening students' social awareness. Second, the success of the school climate transformation is influenced by supporting factors such as the commitment of the madrasah principal, the active role of teachers, religious culture, and parental support, while inhibiting factors include low awareness of some students, the influence of digital media, limited mentoring, and less than optimal synergy between schools and families. Third, the mentoring of the Love Curriculum has positive implications in the form of increased harmonious relationships between teachers and students, the creation of a conducive learning atmosphere, the development of tolerance and social awareness, and the formation of a humanistic and religious school culture. This study confirms that the Love Curriculum can be an effective strategy in strengthening character education and improving the school climate in madrasas.